2017
DOI: 10.1016/j.pmedr.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between screen time and depression among US adults

Abstract: Epidemiological surveys conducted in general populations have found that the prevalence of depression is about 9% in the United States. World Health Organization has projected that depression will be leading cause of disease burden by the year 2030. Growing evidence suggests that sedentary lifestyle is an important risk factor of depression among adults. The relationship between television watching/computer use and depression in US adults is still unknown. The objective of this study was to assess the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 34 publications
2
90
1
2
Order By: Relevance
“…In fact, participants who had inadequate physical social interaction and a reduction of face-to-face communication during the pandemic might be more prone to depressive symptoms. Spending more time using screens was significantly associated with developing depressive symptoms [44]. The reduction of time spent having social interactions was correlated to the depressive symptoms [45], whilst infrequent social interaction could also predict higher depressive symptoms [46].…”
Section: Discussionmentioning
confidence: 90%
“…In fact, participants who had inadequate physical social interaction and a reduction of face-to-face communication during the pandemic might be more prone to depressive symptoms. Spending more time using screens was significantly associated with developing depressive symptoms [44]. The reduction of time spent having social interactions was correlated to the depressive symptoms [45], whilst infrequent social interaction could also predict higher depressive symptoms [46].…”
Section: Discussionmentioning
confidence: 90%
“…On the contrast, the results about computer use are less consistent. While some studies found a positive association between computer use and depression (Madhav, Sherchand, & Sherchan, 2017;Sanchez-Villegas et al, 2008), some were not (Thomée, Eklöf, Gustafsson, Nilsson, & Hagberg, 2007;Thomee, Harenstam, & Hagberg, 2012). Several studies even suggested possible beneficial effects of computer use on cognition and mental health (Kesse-Guyot et al, 2012;Shaw & Gant, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This was because the KMPS does not collect any detailed information on health conditions of each participant. Additionally, recent studies have reported the adverse effects of excessive screen time on mental health, which may also affect the incidence of obesity [ 22 , 39 ]. Therefore, the joint association of screen time and physical activity with obesity must be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…The average daily screen time was categorized into 4 groups based on the distribution of the average daily screen time (< 2, ≥ 2 to < 4, ≥ 4 to < 6, and ≥ 6 hours/day) to stabilize regression estimates. Similar categorizations of average daily screen time have been used in previous studies [ 9 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation